Indonesian law - Lindsey, Timothy, 1962-; Butt, Simon (Oxford : Oxford University Press, 2018)
This text offers the first comprehensive survey in English of the Indonesian legal system. It includes clear and concise introductions to complex substantive Indonesian law and commentaries on issues that will interest both academics and practitioners.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 20, 2018).
Keywords: Law -- Indonesia; Law; Laws of specific jurisdictions & specific areas of law